TRANSFERRIN POLYMORPHISM IN FOUR LOCAL BREEDS OF GOAT IN CENTRAL JAVA, INDONESIA - E. Kurnianto; S. Sutopo; D. Samsudewa; E. Purbowati; D.R. Dewanti; G.D. Brata (Diponegoro University, 2013)
The objectives of this study were to determine the gene frequency and individual heterozygosity oftransferrin in four local breeds of goat in Central Java-Indonesia. The number of blood samples weretaken from 96 heads of goat, in which each of breeds were 24 samples, those were Kejobong(Purbalingga regency), Ettawa Grade (Purworejo regency), Kacang (Grobogan regency) and Jawarandu(Pemalang regency). Polyacrilamide Gel Electrophoresis was performed to detect the bands of bloodplasm protein. Gen frequency was calculated using general formula of population genetics. Estimatedheterozygosity and individual heterosizygosity were calculated to analysis the equilibrium condition oftransferrin. Result showed there was two allele of transferrin, namely TfA and TfB. Gene frequency ofTfA was higher than that of TfB. Transferrin gene and genotypes were in disequilibrium of Hardy-Weinberg Law.